Medicinal plants of the Himalayan Tral region of Kashmir, India: an ethnobotanical study of their diversity, use patterns, and health implications - Mir, Aaqib Maqbool; Mir, Bilal Ahmad; Peer, Latif Ahmad (Ethnobotany Research and Applications, 2024)
Background: For the tribal inhabitants of Tral, a location in Indian Kashmir’s Pulwama district, medicinal plants constitute a significant source of healthcare. Being underexplored for traditional knowledge and usage of medicinal plants, an ethnobotanical survey was carried out to document the diversity, usage, and cultural significance of medicinal plants in this area. Methods: The data were collected from 57 informants using group discussions, questionnaires, and interviews. Data was analyzed through use value, fidelity level, and informant consensus factor calculations. Results: Forty-seven plant species from twenty-seven families were recorded, with roots and leaves being the frequently used plant parts. Decoctions and infusions were the preferred methods for treating various ailments. The highest informant consensus factor of 0.85 was recorded for gut disorders and treated with 25 plant species, whereas the lowest informant consensus factor of 0.36 was observed for skeletomuscular disorders and treated with 10 species. Ocimum tenuiflorum showed the highest use value of 0.46, whereas Phytolacca acinosa exhibited the lowest use value of 0.05. The highest fidelity value of 100% was found for Datura stramonium, Phytolacca acinosa, Sibbaldia cuneata, Arisaema jacquemontii, Rhododendron campanulatum, Bergenia ciliata, Salvia hians, Valeriana jatamansi against helminths, beef worms, skin rashes, abscesses, hypersomnia, deep wounds, arthritis and throat pain, respectively. Rumex acetosa exhibited the lowest fidelity value of 33% against constipation. Conclusions: This study presents a comprehensive analysis of the traditional knowledge and use patterns of medicinal plants in the Himalayan Tral region of Kashmir, serving as a foundation for further research in ethnobotany and pharmacology. Keywords: Ethnomedicine, informant consensus, fidelity value, Kashmir Himalaya